Modifications of the EEG produced by the tetraethylammonium ion (Revista Española de Fisiología, 1950)
The authors investigate in rabbits curarized and without anaesthesia the electroencephalpgraphic effects of tetraethylammonium. They observe that the endovenous injection at the maximum doses tolerable produces only slight modifications, characterized by discharges of waves of greater amplitude and frequency than in the control graphic. They essay comparatively the effect of the intracisternal injection of TEA in the quantity just necessary to obtain a concentration in the ccrebrospinal fluid, equal to that corresponding to the endovenous injection. In the latter case, the effect on the EEG is approximately the same as that obtained with the endovenous in jection.The intracisternal injection at higher concentrations provokes the appearance of discharges of great amplitude and greater frequency than in the control graphic. From the results the authors deduct that the effect corresponda to a direct action of the substance in the brain.